(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces a new double hybrid transform yielding single integral transforms and their generalizations. The main purpose of this study is to propose the most common form for generalized transformations in terms of Hybrid Sumudu and Shehu transforms. In this paper, we introduce a just invented transform and research its basic characteristics such as existence, inversion, along with related theorems. The study also introduces novel results with respect to partials and generalizes the double convolution theorem. Furthermore, it uses the developed properties and theorems to solve specific kinds of differential equations that have very important applications in physics and science. The purpose of this research is to show the applicability and efficiency of a novel transform in solving differential equations with multiple variable to solve.